Resource economics - "Conrad, Jon M" (New Delhi, 2011)
The Book Covers Basic Concepts, Shows How To Set Up Spreadsheets To Solve Simple Dynamic Allocation Problems, And Presents Economic Models For Fisheries, Forestry, Nonrenewable Resources, And Stock Pollutants . Examines The Maximin Utility Criterion When The Utility Of A Generation Depends On Consumption Of A Manufactured Good, Harvest From A Renewable Resource, And Extraction From A Nonrenewable Resource. These Problems Help Make Concepts Operational, Develop Economic Intuition, And Serve As A Bridge To The Study Of Real-World Problems In Resource Management.
Keywords: Natural resources-Management-Mathematical models